Study of Activation Energy of Methoxy Acetic Acid in Different Solvents - Murthy, M.B.R.; Daya Sagar, B.S.; Barman, P.B. (Asian Journal of Chemistry, 2010)
Dielectric measurements at 9.318 GHz on methoxy acetic acid are carried out at room temperature in three different solvents. These data are used to evaluate relaxation times of solute molecule in three solvents. The difference in activation energies for a pair of solvents is determined. The result is used to explain the difference of relaxation time of the same solute molecule in various solvents.